Sistem Pendukung Keputusan Penerimaan Bantuan Pangan Non-Tunai (BPNT) Menggunakan Metode Simple Multi-Attribute Rating Technique di Desa Kelapapati - Muhammad Firqi Saputra; Ryci Rahmatil Fiska (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
Social assistance is a form of government concern to alleviate poverty. This assistance can be in the form of money, clothing, food, or medicine needed by the community. The purpose of social assistance is to improve the welfare of the community. In providing social assistance, both the local government as the provider and the recipient community must be accountable according to the provisions. Social assistance is regulated in Government Regulation No. 58/2005 and Minister of Home Affairs Regulation No. 13/2006. Kelapapati Village faces challenges in the efficient distribution of social assistance. Manual processes in registration, data management, distribution, and monitoring often lead to problems such as recipient verification errors, misuse, and untargeted distribution. Subjectivity in assessing recipient eligibility also triggers social jealousy. The SMART (Simple Multi-Attribute Rating Technique) method is applied as a solution to improve efficiency. This method prioritizes beneficiaries based on criteria such as number of dependents, income, employment, and single parent status.